2021
DOI: 10.1007/s00227-021-03844-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation in herbivore grazing behavior across Caribbean reef sites

Abstract: Herbivorous fish can increase coral growth and survival by grazing down algal competitors. With coral reefs in global decline, maintaining adequate herbivory has become a primary goal for many managers. However, herbivore biomass targets assume grazing behavior is consistent across different reef systems, even though relatively few have been studied. We document grazing behavior of two scarid species in Antigua, Barbuda, and Bonaire. Our analyses show significant differences in intraspecific feeding rates, tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Protection of herbivorous fishes, such as parrotfishes, has been the focus to alleviate the algal problems on Caribbean coral reefs (Bellwood et al 2004;Mumby 2006). Not all herbivores are the same in reducing algae, as they have different behavioral and morphological traits which affect what they consume and the efficiency of their grazing (Carpenter 1986;Burkepile & Hay 2011;Wilson et al 2021). Studies have shown that herbivorous fishes are not effective in reducing macroalgae, as they tend to target more palatable algae, like filamentous turf algae (Burkepile & Hay 2010;Briggs et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Protection of herbivorous fishes, such as parrotfishes, has been the focus to alleviate the algal problems on Caribbean coral reefs (Bellwood et al 2004;Mumby 2006). Not all herbivores are the same in reducing algae, as they have different behavioral and morphological traits which affect what they consume and the efficiency of their grazing (Carpenter 1986;Burkepile & Hay 2011;Wilson et al 2021). Studies have shown that herbivorous fishes are not effective in reducing macroalgae, as they tend to target more palatable algae, like filamentous turf algae (Burkepile & Hay 2010;Briggs et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These variations may profoundly impact the structure and function of coral reef ecosystem. For example, the loss of herbivorous fish can hinder recovery of bleached coral and accelerate regime shifts from coral-to algae-dominated states (Rempel et al, 2020;Wilson et al, 2021). Large carnivorous fishes are the top predators in coral reef and control the structure of the ecosystem through predation, and their loss can lead to the explosion of bait species and destroy the balance of coral reef (Roberts, 1995;Bellwood et al, 2004).…”
Section: Daytonmentioning
confidence: 99%
“…Therefore, the knowledge of reef fish feeding is of great significance for protecting fishery resources and diagnosing health status of coral reefs (Letourneur et al, 2013;Hempson et al, 2017;Morillo-Velarde et al, 2018). Dividing reef fish into different trophic groups according to their prey is helpful to study their ecological roles and how fishing and climate alter the structure of reef fish (Gao et al, 2014;Wilson et al, 2021;Dai et al, 2022). For example, herbivorous fishes in coral reef can inhibit algal overgrowth and promote coral growth, which is important for the recovery of bleached coral (Cramer et al, 2017;Rempel et al, 2020;Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivorous species most likely are not the exception; however, this has been rarely assessed around the globe, particularly at large biogeographical scales. Among the few studies, the parrotfishes Sparisoma viridae and Scarus vetula have shown significant variation in bite rates among populations in coral reefs of Barbuda, Antigua and Bonaire (Wilson et al 2021), and populations of Leptoscarus vaigiensis differed in diet diversity and breadth across coral reefs of Kenya (Locham et al 2015), while the surgeonfishes Acanthurus tractus and Acanthurus coeruleus had different proportions of bites taken on different food items, such as turf, epiphytes, or sessile invertebrates among coral reefs of the Florida Keys (Duran et al 2019).…”
Section: Introductionmentioning
confidence: 99%